Profile of graduates of the careers of the Faculty of Economic Sciences - Gerda Palacios de Asta (Población y Desarrollo, 2019)
In this article, it presents an analysis of the profile of graduates based on a study of the different careers of the Faculty of Economic Sciences of the National University of Asuncion (FCE.UNA) carried out in 2016. The study was aimed at describe the conditions of occupational insertion, educational continuity and satisfaction with regard to the characteristics of the educational offer and the graduate profile of the graduates by careers. The descriptive methodology, with a quantitative approach, applied questionnaires to an intentional sample of graduates from different years. As a main result, the graduates of all the careers have a satisfactory perception (between good and excellent) in relation to the generic competences, and the specific competences in their graduation profiles.